AVALIAÇÃO DAS PROPRIEDADES MECÂNICAS E ADESIVAS DE CIMENTOS RESINOSOS UTILIZADOS NA CIMENTAÇÃO DE PINOS INTRARRADICULARES - Mora, Camilo Andrés Pulido (2017)
The aims of the study were: 1) to evaluate the bond strength (μTBS) and light transmission (LT) of individualized posts with different composite resin translucency,as well as the Vickers microhardness (VHN) of a self-adhesive resin cement. 2) to compare the shrinkage strain (SS), shrinkage rate (SR) and VHN of a conventionalcement and a self-adhesive one in the apical and cervical thirds of the root canal. 3) to compare the μTBS, VHN and nanoinfiltration (NI) immediately and after 3 years of a conventional resin cement and a self-adhesive one used in fiberglass post cementation. For the experiment 1, 70 lower premolars (n = 10) were selected and divided into 5 groups according to the resin translucency used for the post individualization: ideal adaptation (Positive control), high translucency composite resin (HT), Medium translucency composite resin (MT), high opacity composite resin (RAO) and pooradaptation (Negative Control); and cemented with dual resin cement RelyX U200 (3M / ESPE). One week later the BS, VHN and LT were evaluated.For experiment 2, 56 lower premolars were selected and endodontically treated. The teeth were randomly divided into 2 groups (n = 28) according to the resin cement used: RelyX ARC Group (3M / ESPE) and U200 Group: RelyX U200 (3M /ESPE). After that, 28 specimens (n = 14 per group) were sliced and submitted to VHN, BS and NI tests; And the other 28 specimens were sliced and stored in distilled water at 37 ° C for testing after 3 years. For experiment 3, 34 lower premolar teeth were selected and endodontically treated; Were then randomly divided into two groups (n = 14) according to the resin cement used: RelyX ARC Group (3M / ESPE) and U200 Group: RelyX U200 (3M / ESPE). Before the insertion of the resin cement in the root canal, two fiber optic sensors with Bragg gratings were placed in the post to measure cement deformation in the coronary and apical regions of the root canal. Data from each group (n = 10) were kinetically analyzed for polymerization Shrinkage strain (PS). The Shrinkage rate (SR) was calculated by numerical differentiation of the shrinkage data as a function of time. The experiments were analyzed by ANOVA and Tukey's test (a= 0.05). Experiment 1 showed a significant influence of resin translucency on resin cement properties. High translucency, promoted high μTBS and VHN. Experiment 2 showed that ARC had higher values of μTBS and VHN in the cervical third, but U200 presented the highest values after 3 years. In experiment 3 there was no difference in PS between the cements analyzed, but the ARC presented higher SR in both thirds. For the VHN, no significant difference in the cervical third was found, but U200 presented higher values in the apical third.